Puzzles of vision and art. Are we all synaesthetes? (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2017)
The meaningful appearances of natural forms, intrinsically provided with meaning, are primary ecological facts for humans and non–human living beings. Only in recent years, however, perception studies have developed research pointing to the qualitative, and multimodal aspects of the experience. Specifically, the debate is now moving to the field of cross–modality, studying the connections between any given sensory feature in one modality (for example, color) and a sensory feature in another modality (for example, sound). Initially prompted by interest in the field of synesthesia, studies have begun considering similar phenomena occurring in the general population. Several hypotheses have been presented to explain the nature of such associations. A recent review of the field has drawn a distinction among structural correspondences (due to neural correlates, hence potentially universal), statistical correspondences (due to learning, hence potentially influenced by different environments), and semantic correspondences (due to language influence, hence potentially different among cultures). A growing number of researchers explains associations in terms of patterns of qualitative similarity present in different sensory modalities and perceived as such: for example, hot and cold, sad and happy, and pleasant and unpleasant, are connotative properties of both sounds and colors, something about which the arts have always been aware. This means that what is at stake is not semantic information projected top–down into other domains, but qualities intrinsic to perceived phenomena. This position obviously does not preclude investigation of correlations at neuronal level or the presence of cognitive dimensions due to learning, language, and human symbolic activities. My contribution presents a survey of the results of recent studies in cross–modality. Specifically, I show the existence of cross–modal associations between geometric shape (and parts of, such as angles) and color, morphological shapes and color, materic paintings and classical Spanish music, abstract paintings and virtual tactile perception. These findings shed light on our relationship with the environment, and on the correspondences between perceptual and pictorial space.